The Handbook of Evolutionary Psychology 2015
DOI: 10.1002/9781119125563.evpsych247
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Political Psychology

Abstract: Politics is the process of negotiating conflicts of interest. Evolutionary political psychology is the field concerned with the application of evolutionary psychology to the study of politics. This application often entails a two‐step process: (1) dissecting the adaptive problems of conflicts of interests and building testable predictions on the structure of the corresponding adaptations for political behavior; and (2) analyzing how these adaptations operate under the evolutionarily novel conditions of mass po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
38
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 70 publications
5
38
0
2
Order By: Relevance
“…If social life is a game, then politics is the process of establishing and negotiating the rules of that game, defining who is entitled to get what, when, and how (Petersen, 2015). Politics conceived in this way extends far back into our species' evolutionary history (see De Waal, 1982), and there has been a recent surge of studies arguing that human biology shapes the way modern humans represent and think about modern politics (for reviews, see Hatemi & McDermott, 2011;Hibbing et al, 2013;Petersen 2015).…”
Section: The Psychology Of Politicsmentioning
confidence: 99%
“…If social life is a game, then politics is the process of establishing and negotiating the rules of that game, defining who is entitled to get what, when, and how (Petersen, 2015). Politics conceived in this way extends far back into our species' evolutionary history (see De Waal, 1982), and there has been a recent surge of studies arguing that human biology shapes the way modern humans represent and think about modern politics (for reviews, see Hatemi & McDermott, 2011;Hibbing et al, 2013;Petersen 2015).…”
Section: The Psychology Of Politicsmentioning
confidence: 99%
“…In contrast to the General Orientations Model (Haidt 2012;Hibbing, Smith, & Alford 2013, 2014Jost, Federico, & (Petersen 2015;Weeden & Kurzban 2014). In this paper, we reviewed evidence that the bulk of the US population shows little tendency to align opinions on a single left-right axis across religious and racial/economic domains.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we've suggested that views on government economic redistribution relate more to socioeconomic status and the extent to which one's private support network reduces one's need for public safety nets (Weeden & Kurzban 2014). When opinions across such issue domains align in ideologically consistent waysthat is, when individuals are either liberal on various types of issues or conservative on various types of issues-we argue, echoing Petersen's (2015) view, that it's typically either, first, because the underlying domain-specific interests happen to align or, second, because the political coalitions happen to become organized such that various liberal constituencies are allied in competition against various conservative constituencies.…”
mentioning
confidence: 99%
See 2 more Smart Citations